Reducing the Gender Gap in Mental Rotation - Schoen, Shaelyn; Heimerl, Shaina (My University, 2013)
Mental Rotation (MR) is the ability to visualize an object rotating around its axis (Shepard & Metzler, 1971). Success in the Science, Technology, Engineering, and Mathematics (STEM) domains are strongly associated with Mental Rotation skills (see Wai, Lubinski & Benbow, 2009 for a review of 50 years of this literature). Historically, there is a substantial male-female discrepancy, favoring males, in both STEM domain (Webb, Lubinski & Benbow, 2007) and MR performance (i.e., Flahatery, 2005; Linn & Petersen, 1985; Voyer, Voyer & Bryden, 1995). The purpose of this limited literature review was to explore approaches that have been shown to reduce this gender gap in MR performance.
Color poster with text and images.
Keywords: Literature review; Spatial visualization ability; Posters